Short versus long video-based lectures as a tool for faculty development during COVID-19 pandemic - Elsamanoudy, Ayman Z.; Aboukamer, Rasha A.; Hassanien, Mohammed A. (International Journal Of Community Medicine And Public Health, 2021)
With emerge of the COVID-19 pandemic, video-based lectures (VBLs) was widely used as an effective online faculty development tool. VBLs varies from short videos (5-minute) to the long one (1-2 hours). So, the current study aims to evaluate the effectiveness of long VBLs versus short VBLs. A total of 21 short (9) and long (12) VBLs were produced, in 2020, by the authors. The metadata for all of VBLs was downloaded from YouTube [VBLs overview data, audiences’ engagement data, and audience retention (AR) report]. The viewership data included the number of views (4800), watch time by hours (173.6), males to females’ ratio (79/21), the number of the subscribers (157), the video length (2.9±1.2 minutes), number of viewers (241.1±157.8), and the watch time (5.1±3.3 hours). The audience retention is presented as average view duration (1.1±0.4 hours) and average percentage view (42.8±7.9%). Lastly, audience engagement is represented by the number of subscribers (6.4±7.4), likes (9.7±8.0), and dislikes (0.3±0.7). The comparison of the mean audience retention and engagement between short and long VBLs showed that short VBLs had significantly higher number of subscribers and likes as well as the average percentage views in comparison to long VBLs. We could conclude that short VBLs are more effective and efficient as a regard audience retention and engagement. Moreover, the more use of advanced technology for video development makes it more engaging.